A non-fired pure magnesium slag carbon-absorbing building block without hidden dangers of volume stability and a manufacturing method thereof
By digesting and carbonizing the magnesium slag, a carbon-absorbing block without volume stability is prepared without volume stability, which solves the volume stability of magnesium slag in the field of building materials, improves the strength and carbonization of the material, and realizes the realization of the Efficient resource utilization of magnesium slag.
Patent Information
- Application Number
- CN202410682465.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-05-29
AI Technical Summary
The application of existing magnesium slag in the field of building materials has volume stability problems, resulting in safety hazards and insufficient material strength, limiting its large-scale application in building materials.
By digesting and treating magnesium slag and combining with the carbonization process, a carbonization block without volume stability is prepared. The method includes grinding the magnesium slag and mixing it with water, heating and digesting MgO, pouring and carbonizing after natural cooling, and improving the strength and carbonization of the material through multiple carbonization and water immersion cycles.
It effectively solves the volume stability problem of magnesium slag in the building materials field, improves the strength and carbonization of materials, realizes efficient resource utilization of solid waste magnesium slag, and enhances the competitiveness of products.
Smart Images

Figure CN118580055B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a non-fired pure magnesium slag carbon-absorbing building block without hidden dangers of volume stability and a manufacturing method thereof. Background Art
[0002] At present, the silicothermic process is the main technology for raw magnesium smelting in my country, and its output accounts for more than 90% of the national raw magnesium output and more than 80% of the world's raw magnesium output. More than 6.5 million tons of smelting reduction slag are newly produced each year (hereinafter referred to as magnesium slag).
[0003] According to the document "Classification and Code of General Solid Waste" (GB / T 39198-2020) promulgated in 2020, magnesium slag is classified as solid waste No. 260-001-54. With the gradual advancement of my country's ecological civilization construction, the concept of green development has penetrated into all walks of life. In recent years, the country has continuously increased the intensity of environmental protection supervision and law enforcement. The waste of resources and environmental pollution caused by magnesium slag have become more and more prominent in the green development process of the magnesium smelting industry. In order to utilize magnesium slag resources, domestic and foreign universities, research institutes and enterprises have carried out some applied technology research and development work, such as using magnesium slag to produce cement, using magnesium slag to make bricks, using magnesium slag as a desulfurizer, and using magnesium slag as a soil modifier. Compared with other application fields, the application of magnesium slag in the field of building materials has the potential for larger-scale application. This is also an urgent need for large-scale application of solid waste under the background of sustainable development and dual carbon requirements. However, during the cooling process of magnesium slag, its main component Ca2SiO4 will transform from β-crystal to γ-crystal, which greatly reduces the reactivity of magnesium slag. Therefore, it is difficult for magnesium slag to generate high-strength materials through hydration like cement. At the same time, there is 10-15% MgO in magnesium slag, which loses its reactivity due to overburning. It does not undergo rapid hydration reaction in the process of preparing unburned bricks or blocks. Instead, it slowly generates Mg(OH)2 with a lower density during the service life of unburned bricks or blocks, causing volume expansion and serious cracking of the wall. Therefore, using magnesium slag as a building material will pose a huge safety hazard. This phenomenon is also called the volume stability problem.
[0004] Chinese patents CN113321477B, CN104478256B, and CN114956774A all disclose methods for producing building materials using industrial waste slag (including magnesium slag) as raw materials, which can replace the high energy consumption and high carbon emission process of traditional cement by mixing industrial waste slag with high calcium content with fly ash, carbonizing and low temperature steaming. However, considering the different sources of industrial waste slag, the MgO content in magnesium slag varies greatly, and there are also certain production temperature differences. For example, magnesium slag is produced by smelting at 1200℃ for more than 10 hours, and the remaining MgO in the slag is in an overburned state, which is easy to cause volume stability problems. Although the product of the carbonization process is MgCO3, this process is not a volume expansion process and there is no volume stability problem, but the carbonization process generally has the situation of incomplete carbonization or the generation of the intermediate product MgCO3·3H2O (mentioned in CN104478256B), and the remaining MgO and MgCO3·3H2O will undergo the following reaction under natural conditions. According to Table 1, by comparing the reactant density and the product density, it can be seen that the following reactions are all volume expansion reaction processes. Therefore, it can be seen that the carbonization process still cannot avoid the volume stability problem.
[0005] MgO+H2O→Mg(OH)2
[0006] 2MgO+MgCO3·3H2O→3Mg(OH)2+CO2
[0007] 2MgCO3+MgCO3·3H2O→3Mg(OH)2+3CO2
[0008] 4MgCO3·3H2O→(MgCO3)3Mg(OH)2(H2O)3+CO2+8H2O
[0009] (MgCO3)3Mg(OH)2(H2O)3→MgCO3·3H2O+2MgCO3+Mg(OH)2
[0010] In addition, even if MgO is completely converted into MgCO3, it will also convert into Mg(OH)2 under the condition of CO2 partial pressure ≤ 0.0003atm, resulting in volume expansion.
[0011] Table 1 Summary of the density of different magnesium metal compounds
[0012] Substance name MgO <![CDATA[MgSiO3]]> <![CDATA[MgCO3]]> <![CDATA[Mg(OH)2]]> Basic magnesium carbonate <![CDATA[Density (g / cm 3 )]]> 3.58 3.19 3 2.36 2.16
[0013] Chinese patent CN102320801B pre-autoclaves magnesium slag. Although the function of this step is not mentioned, this step can effectively convert overburned MgO in magnesium slag into Mg(OH)2. However, the patent requires a pre-treatment pressure of 0.8-1MPa, and the steam temperature corresponding to the saturated steam pressure is 170-180°C. The high-temperature autoclave condition will cause the main component Ca2SiO4 in the slag to be hydrated in large quantities to form a hydration product with a stable structure. At this time, dry grinding will destroy the structure of the hydration product, and the magnesium slag will lose its ability to be rehydrated and formed, and needs to be mixed with red mud or other materials with bonding ability; at the same time, the carbonization ability of the stable hydration product is low. This patent does not consider the carbonization of slag during the natural cooling process and the weakening of the carbonization ability of magnesium slag after high-temperature autoclaving. The above problems will weaken the carbon fixation ability and strengthening effect of magnesium slag. At the same time, it is necessary to mix with other materials with bonding ability, or press molding, which will reduce the utilization rate of magnesium slag.
[0014] In summary, the existing application methods of magnesium slag in building materials have not completely solved the volume stability problem caused by magnesium slag, so the current application of magnesium slag in the field of building materials is still only as a small amount of cement additives, and it is difficult to use it in large quantities. Summary of the invention
[0015] In view of the above-mentioned defects of the prior art, the present invention provides a carbon-absorbing building block made of pure magnesium slag without burning hidden dangers of volume stability and a method for making the same, so as to solve the volume stability problem existing in the existing application technology of magnesium slag in the field of building materials, broaden the application of magnesium slag in the field of building materials, and in the process of realizing the resource recycling of solid waste magnesium slag, enable it to have considerable carbon absorption capacity, greatly improve the material strength without any binder, so that it has higher product competitiveness under the background of sustainable development and dual carbon requirements.
[0016] Based on the above purpose, the present invention adopts the following technical solutions:
[0017] A method for manufacturing a non-fired pure magnesium slag carbon-absorbing building block without hidden dangers of volume stability comprises the following steps:
[0018] (1) Raw material preparation
[0019] ball-milling the magnesium slag to obtain ground magnesium slag;
[0020] (2) Stirring and mixing
[0021] The ground magnesium slag is mixed with water to form a slurry, wherein the water-slag mass ratio is 0.3 to 0.8 by weight;
[0022] (3) Digestion of MgO
[0023] The slurry is sealed, stirred, heated to 100-180° C., kept warm for 3-8 hours to decompose MgO, and cooled naturally;
[0024] (4) Obtaining water-saturated slurry
[0025] Stop stirring, let the slurry obtained in step (3) stand, remove the floating slurry on the surface, stir the remaining slurry evenly, and take the stirred slurry to test the moisture content;
[0026] (5) Slurry pouring and vibration
[0027] The slurry obtained in step (4) is stirred evenly and then poured into a mold. After pouring, the vibration time needs to be adjusted according to the different fluidity of the slurry;
[0028] (6) Pre-curing
[0029] The blocks after pouring are stopped for pre-curing at a temperature of 25-50°C, a humidity of 20-40%, and a curing time of 1-2 days;
[0030] (7) Demolding and gas carbonization
[0031] De-mould the pre-cured blocks, dry them naturally until the moisture content is less than 20%, and then place them in a CO2 atmosphere for curing for 4 to 24 hours;
[0032] (8) Repeated gas carbonization
[0033] The carbonized blocks in step (7) are immersed in water, taken out after immersion, the surface moisture is wiped off, and the blocks are placed in a CO2 atmosphere again for curing for 4 to 24 hours.
[0034] Furthermore, in step (1), the magnesium slag is a reduction slag produced by silicon thermal magnesium smelting. Preferably, in step (1), the magnesium slag is ball-milled to 80-150 mesh. Since the main components of the magnesium slag will be slightly hydrated during the digestion process, the magnesium slag particles will increase. The finer the particles, the larger the surface area for carbonization reaction and the higher the material strength, but its hardening shrinkage in the air is also greater, so the initial fineness of the magnesium slag needs to be controlled within an appropriate range to improve the uniformity of the material and the degree of carbonization.
[0035] Wherein, in step (3), the slurry is sealed and heated to 100-180°C, and the water in the slurry evaporates to form high-temperature saturated steam, and the high-temperature saturated steam pressure is 0.1-0.62MPa (in this process, heat source water can also be directly used to fill the space above the slurry to form a high-temperature saturated steam pressure). After testing, magnesium slag slurry can realize the transformation of overburned MgO to Mg(OH)2 under the condition of 100-180°C, so that it exists in the slag in the form of minimum density and maximum volume, thereby eliminating the volume expansion problem of magnesium slag as a building material after solidification. Preferably, when the MgO content in the magnesium slag is ≤10wt%, the digestion temperature is ≥100°C; when the MgO content in the magnesium slag is ≤12wt%, the digestion temperature is ≥130°C; when the MgO content in the magnesium slag is ≤14wt%, the digestion temperature is ≥160°C.
[0036] The present invention performs digestion in the form of slurry, and the amount of water added must be greater than the amount of water consumed in the digestion process to meet the water required for the digestion process and ensure that the slurry has a certain flowability. The digested slurry does not need to be dried and ground and then watered (this will destroy the bonding ability of the hydration product), and can be used directly, which can maximize the bonding ability of the hydration product and provide more early strength.
[0037] The digestion process of step (3) of the present invention is performed by stirring the slurry at a speed of 10 to 200 rpm, and the stirring action starts after sealing and continues until the natural cooling is completed. Stirring during the digestion process makes the slurry more uniform, which can prevent the self-compacting effect of the fine powder from hindering the penetration of water, resulting in uneven water distribution, incomplete digestion, and agglomeration during the high-temperature digestion process.
[0038] Furthermore, in step (4), the digested slurry is allowed to stand for at least 1 hour, and after removing the surface slurry, the remaining slurry is stirred evenly. Considering that the amount of water added during the digestion process is greater than the amount of water consumed, and the slurry after digestion will be in the state of a non-Newtonian fluid, standing the slurry can allow excess water to secrete out. Removing the secreted slurry to obtain a water-saturated slurry can avoid cracking caused by excessively high water content and prevent the problem of cracking during the solidification process of the block.
[0039] Furthermore, in step (6), the curing time needs to be set according to the water-slag ratio, and the curing time does not exceed 48 hours. Blocks with too high humidity are difficult to solidify and form, and too high temperature causes water loss too quickly, which can easily lead to the appearance of drying cracks. Therefore, the curing conditions are controlled to: temperature 25-50°C, humidity 20-40%, to prevent cracking of blocks during curing.
[0040] Furthermore, in step (7), the blocks are demoulded after pre-curing, and after demoulding, the blocks are naturally dried until the moisture content is less than 20%. If the moisture content of the blocks is too high during carbonization, the intense heat release during the carbonization process will cause the excess water to evaporate rapidly, and the dense blocks have fewer pore channels and cannot meet the requirement for a large amount of water to escape, which will cause the blocks to burst. The moisture content of the naturally dried blocks is from the inside to the outside, from high to low. The external blocks are in a dry state and are not easy to carbonize and block the gas channels. The internal moisture content is moderate. At this time, the water evaporated by carbonization can escape smoothly, so it is necessary to control the moisture content of the blocks before the initial carbonization.
[0041] Furthermore, in step (7), the building blocks dried to a moisture content of less than 20% are placed in a 0.1 MPa to 0.4 MPa CO2 atmosphere for curing for 4 to 24 hours.
[0042] Furthermore, in step (8), the blocks are immersed in water, excess water on the surface is removed after immersion, and the blocks are placed in a 0.1MPa-0.4MPa CO2 atmosphere for curing for 4-24 hours, at which time the exterior begins to be carbonized. Repeating the immersion and carbonization actions and increasing the carbonization pressure can improve the carbonization degree and strength of the blocks and avoid the problem of carbonization and cracking of dense blocks.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) Solve the volume stability problem of magnesium slag in the field of building materials by digesting and treating magnesium slag; open up the application of magnesium slag in the field of building materials; avoid the safety hazards caused by volume stability; realize the effective utilization of solid waste and regain economic value.
[0045] (2) The digestion process is combined with carbonization. Under the background of sustainable development and dual carbon requirements, CO2 emissions are more strictly restricted. The present invention can effectively reduce CO2 emissions in the industry.
[0046] (3) Combining the digestion and carbonization of magnesium slag can significantly improve the strength of magnesium slag blocks, which can enhance the market competitiveness and economic value of magnesium slag blocks.
[0047] (4) Dissolve in the form of slurry to improve the utilization rate of magnesium slag; form blocks without any additives or bonding materials (such as cement, lime, clay).
[0048] (5) By changing the digestion conditions and adapting to the differences in smelting process parameters of each factory, the magnesium slag produced by different magnesium smelters can be reused, which is more instructive for practical applications.
[0049] (6) By controlling the moisture content of the blocks and circulating pressurized carbonization, the problem of carbonization and cracking of dense blocks can be avoided, and the carbonization degree of magnesium slag blocks can be improved.
[0050] (7) During the digestion process, the slurry is stirred at a speed of 10-200 rpm (the stirring action continues until the natural cooling is completed) to improve the uniformity of the material and prevent self-compacting and agglomeration.
[0051] (8) The magnesium slag is ball-milled to 80-150 meshes to improve the uniformity of the material and the degree of carbonization.
[0052] (9) Allow the dissolved slurry to stand, remove the surface slurry, and stir the remaining slurry evenly to prevent cracking during the solidification process of the blocks.
[0053] (10) The curing process protection of the present application can prevent the problem of cracking of blocks during the curing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The hydration of MgO in the magnesium slag of Example 1 at different digestion temperatures;
[0055] Figure 2 TG and DTG curves of the carbonized test pieces at different digestion temperatures in Example 2;
[0056] Figure 3 Middle: Figure (a) shows the appearance of the unautoclaved test block and the test block autoclaved twice from bottom to top; Figure (b) MS-H shows the strength of uncarbonized magnesium slag at different digestion temperatures, and MS-HC shows the strength of carbonized magnesium slag at different digestion temperatures. DETAILED DESCRIPTION
[0057] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0058] First, according to the MgO content in the magnesium slag, the inventors conducted a large number of experiments in the early stage to determine the requirements of the digestion temperature for different MgO contents in the magnesium slag. The specific results are shown in Table 2.
[0059] Table 2 MgO content in magnesium slag and digestion temperature range
[0060] Autoclave temperature ≥100℃ ≥130℃ ≥160℃ MgO content in slag (element oxide) ≤10wt%(range) ≤12wt% ≤14wt%
[0061] Example 1
[0062] A method for preparing a non-fired pure magnesium slag carbon-absorbing building block without hidden dangers of volume stability, the preparation process is as follows:
[0063] (1) Raw material preparation
[0064] Five portions of magnesium slag with MgO contents of 9wt%, 11wt%, 12wt%, 13wt% and 14wt% were ball-milled to a particle size of less than 100 mesh.
[0065] (2) Stirring and mixing
[0066] The water-slag mass ratio in the magnesium slag digestion process is 0.4, and the ground magnesium slag obtained in step 1) is stirred and mixed with water to prepare slurry.
[0067] (3) Digestion of MgO
[0068] The slurry in step (2) is sealed, stirred at a speed of 50 rpm (the stirring action continues until natural cooling is completed), and kept at 100°C (MgO content 9 wt%), 120°C (MgO content 11 wt%), 140°C (MgO content 12 wt%), 160°C (MgO content 13 wt%), and 180°C (MgO content 14 wt%) for 5 h, respectively, and then cooled naturally.
[0069] (4) Obtaining water-saturated slurry
[0070] Before slurrying, the slurry obtained in (3) was allowed to stand for 1 hour, and after removing the floating slurry on the surface, the remaining slurry was stirred evenly, and the water content of the stirred slurry was tested.
[0071] (5) Slurry pouring and vibration
[0072] The slurry obtained in (4) is stirred evenly and then poured into a mold. After pouring, the vibration time needs to be adjusted according to the different fluidity of the slurry.
[0073] (6) Pre-curing
[0074] After pouring, the blocks need to be kept still for curing at a temperature of 25°C and a humidity of 20% for 1 to 2 days.
[0075] (7) Demolding and gas pressure carbonization
[0076] After pre-curing, demoulding is completed. After demoulding, the blocks are naturally dried until the moisture content is less than 20%, and then placed in a 0.1MPa CO2 atmosphere for curing for 4 hours.
[0077] (8) Repeated gas carbonization
[0078] The carbonized blocks in step (7) are immersed in water until no bubbles overflow from the block surface, taken out after immersion, the surface moisture is wiped off, and the blocks are placed in a 0.2MPa CO2 atmosphere for curing for 4 hours. The blocks are immersed in water again until no bubbles overflow from the block surface, taken out after immersion, the surface moisture is wiped off, and the blocks are placed in a 0.3MPa CO2 atmosphere for curing for 4 hours.
[0079] This application tests the hydration rate of MgO in magnesium slag at different digestion temperatures for magnesium slag with different MgO contents. The specific results are shown in Figure 1 .according to Figure 1 It can be seen that when the digestion temperature is 100°C, the hydration rate (conversion rate) of MgO is 53%, when the digestion temperature is 120°C, the hydration rate (conversion rate) of MgO is 60%, when the digestion temperature is 140°C, the hydration rate (conversion rate) of MgO is 63%, when the digestion temperature is 160°C, the hydration rate (conversion rate) of MgO is 64%. Figure 1 The hydration of MgO in magnesium slag at different digestion temperatures can adjust the high-temperature digestion conditions of magnesium slag with different MgO contents obtained under different smelting conditions. Generally, the MgO content in magnesium slag is about 10%, and the conversion rate exceeds 50%, which can avoid volume stability problems. Figure 3 The volume stability test results of the blocks obtained at different temperatures are consistent.
[0080] Example 2
[0081] A method for preparing a non-fired pure magnesium slag carbon-absorbing building block without hidden dangers of volume stability, the preparation process is as follows:
[0082] (1) Raw material preparation
[0083] Magnesium slag (Mg oxide content of 9 wt%) was ball-milled to a particle size of less than 80 mesh.
[0084] (2) Stirring and mixing
[0085] The water-slag mass ratio in the magnesium slag digestion process is 0.5, and the ground magnesium slag obtained in step (1) is stirred and mixed with water to prepare slurry.
[0086] (3) Digestion of MgO
[0087] The slurry in step (2) was sealed, stirred at a speed of 80 rpm (the stirring action continued until the natural cooling was completed), kept at 100° C., 120° C., 140° C., 160° C., and 180° C. for 5 h, respectively, and cooled naturally.
[0088] (4) Obtaining water-saturated slurry
[0089] The slurry obtained in (3) was allowed to stand for 1 hour, and after removing the floating slurry on the surface, the remaining saturated slurry was stirred evenly, and the water content of the stirred slurry was tested.
[0090] (5) Slurry pouring and vibration
[0091] The slurry obtained in (4) is stirred evenly and then poured into a mold. After pouring, the vibration time needs to be adjusted according to the different fluidity of the slurry.
[0092] (6) Pre-curing
[0093] After pouring, the blocks need to be stopped for pre-curing at a temperature of 25°C and a humidity of 25% for 1 to 2 days.
[0094] (7) Demolding and gas carbonization
[0095] After pre-curing, demoulding is completed. After demoulding, the blocks are naturally dried until the moisture content is less than 20%, and then the blocks are placed in a 0.1MPa CO2 atmosphere for curing for 4 hours.
[0096] (8) Repeated gas carbonization
[0097] The carbonized blocks in step (7) were immersed in water until no bubbles overflowed from the surface of the blocks. After immersion, the blocks were taken out and the surface moisture was wiped off. The blocks were placed in a 0.2 MPa CO2 atmosphere for curing for 4 h. The obtained blocks (size: 3 cm*3 cm*3 cm, the same below) were respectively recorded as MS-H100℃-C, MS-H120℃-C, MS-H140℃-C, MS-H160℃-C and MS-H180℃-C.
[0098] Figure 2 TG and DTG curves of blocks with different digestion temperatures. Figure 2 It can be seen that the magnesium slag carbonization product (mass is measured as m) mainly has two weight loss sections (room temperature to ~550℃) which is the water loss process, the weight loss is measured as m1, and (550~830℃) is the carbon loss process, the weight loss is measured as m2.
[0099] The carbon fixation amount C can be expressed by C = m1 / (m-m1-m2). The carbon fixation amount of each digestion temperature block is shown in Table 3 below:
[0100] Table 3
[0101] Digestion temperature / ℃ 100 120 140 160 180 Carbon fixation / % 11.11 12.82 17.47 20.02 17.47
[0102] The volume stability was tested in accordance with the requirements of GBT750-1992 Cement Autoclave Stability Test Method by autoclaving at 217℃ for 3h. The results are as follows: Figure 3 As shown in (a), Figure 3 (a) It can be seen that the samples obtained at different digestion temperatures all meet the national standard volume stability requirements.
[0103] Comparative Example 1
[0104] The preparation process is as follows:
[0105] (1) Raw material preparation
[0106] The magnesium slag (Mg oxide content of 9 wt%) was ball-milled to a particle size of less than 80 mesh.
[0107] (2) Stirring and mixing
[0108] The water-slag mass ratio in the magnesium slag digestion process is 0.5, and the ground magnesium slag obtained in step 1) is stirred and mixed with water to prepare slurry.
[0109] (3) Digestion of MgO
[0110] The slurry in step (2) was sealed, stirred at a speed of 50 rpm (the stirring action continued until the natural cooling was completed), kept at 100° C., 120° C., 140° C., 160° C., and 180° C. for 5 h, respectively, and cooled naturally.
[0111] (4) Obtaining water-saturated slurry
[0112] Before pulping, the slurry obtained in step (3) is allowed to stand for 1 hour, and after removing the floating slurry on the surface, the remaining slurry is stirred evenly, and the water content of the stirred slurry is tested.
[0113] (5) Slurry pouring and vibration
[0114] The slurry obtained in (4) is stirred evenly and then poured into a mold. After pouring, the vibration time needs to be adjusted according to the different fluidity of the slurry.
[0115] (6) Pre-curing
[0116] After pouring, the blocks need to be kept still for curing at a temperature of 25°C and a humidity of 20% for 1 to 2 days.
[0117] (7) Demolding and gas pressure carbonization
[0118] After pre-curing, the blocks were demoulded and naturally dried to a moisture content of less than 20%. Uncarbonized blocks at different digestion temperatures were obtained as control samples (size: 3 cm*3 cm*3 cm).
[0119] The compressive strength of the carbonized samples and the unoxidized samples at different digestion temperatures of Example 2 and Comparative Example 1 were tested, and the results are as follows: Figure 3 As shown in (b), MS-H represents the compressive strength of uncarbonized magnesium slag at different digestion temperatures, and MS-HC represents the compressive strength of carbonized magnesium slag at different digestion temperatures. Figure 3 The compressive strength results of carbonized samples and unoxidized samples at different digestion temperatures in (b) are shown in Table 4.
[0120] Table 4
[0121] Digestion temperature / ℃ 100 120 140 160 180 Uncarbonized strength / MPa 0.6618 0.3678 0.6644 1.0359 0.9086 Strength after carbonization / MPa 1.0823 4.4979 8.4695 29.4125 5.5478
[0122] It can be seen from Table 4 that when the digestion temperature is 100℃, the compressive strength of the block is 1.1MPa; when the digestion temperature is 120℃, the compressive strength of the block is 4.5MPa; when the digestion temperature is 140℃, the compressive strength of the block is 8.5MPa; when the digestion temperature is 160℃, the compressive strength of the block is 29.4MPa; when the digestion temperature is 180℃, the compressive strength of the block is 5.5MPa. They are significantly higher than the compressive strength of the uncarbonized block at the same digestion temperature. The above strength changes also show that the autoclave temperature should not be too high. It reflects the rationality of the digestion condition setting of this patent.
[0123] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for producing a non-fired pure magnesium slag carbon-absorbing building block without hidden dangers of volume stability, characterized in that: The steps include: (1) ball-milling magnesium slag to obtain ground magnesium slag; the magnesium slag is a reduction slag produced by silicon thermal process magnesium smelting, and the fineness of the magnesium slag after ball-milling is 80-150 mesh; (2) mixing the ground magnesium slag with water to form a slurry, wherein the water-slag ratio is 0.3-0.8 by weight; (3) The slurry is sealed, stirred, heated to 100-180°C, kept warm for 3-8 hours to digest MgO, and cooled naturally; when the MgO content in the magnesium slag is ≤10 wt%, the digestion temperature is ≥100°C; when the MgO content in the magnesium slag is ≤12 wt%, the digestion temperature is ≥130°C; when the MgO content in the magnesium slag is ≤14 wt%, the digestion temperature is ≥160°C; (4) stopping stirring, allowing the slurry obtained in step (3) to stand, removing the floating slurry on the surface, stirring the remaining slurry to be uniform, and taking the stirred slurry to test the moisture content; (5) The slurry obtained in step (4) is stirred evenly and poured into a mold. After pouring, the vibration time needs to be adjusted according to the different fluidity of the slurry; (6) After pouring, the blocks are placed in a static state for pre-curing at a temperature of 25-50°C, a humidity of 20-40%, and a curing time of 1-2 days; (7) De-mould the pre-cured blocks, dry them naturally until the moisture content is less than 20%, and then place them in a CO2 atmosphere for curing for 4 to 24 hours; (8) Soak the carbonized blocks in step (7) in water, take them out, wipe off the surface moisture, and place the blocks in a CO2 atmosphere for curing again for 4 to 24 hours.
2. The method for making the unburned pure magnesium slag carbon-absorbing building block without volume stability risk according to claim 1 is characterized in that: The digestion process of step (3) is performed by stirring the slurry at a speed of 10 to 200 rpm. The stirring action starts after sealing and continues until natural cooling is completed.
3. The method for making the unburned pure magnesium slag carbon-absorbing building block without volume stability risk according to claim 1 is characterized in that: In step (7) and step (8), the CO2 atmosphere pressure is 0.1 MPa to 0.4 MPa.
4. The unburned pure magnesium slag carbon-absorbing building block without volume stability risk produced by the production method according to any one of claims 1 to 3.
5. Application of the unburned pure magnesium slag carbon-absorbing building block without volume stability risk as claimed in claim 4 in carbon fixation and carbon absorption.
Citation Information
Patent Citations
Method for producing braking-free brick from red mud and magnesium slag used as main materials by press shaping
CN102320801B
Magnesium-calcium carbonate cementitious material and preparation method thereof
CN104478256B
A carbonate building material and its manufacturing method
CN113321477B
Method for preparing building material by utilizing bulk solid waste to synergistically mineralize CO2
CN114956774A
Building forming material produced by taking silicothermic waste residues as raw materials and method for producing building forming material
CN109485360A